Meretas Tabu: Efektivitas Psikoedukasi dalam Meningkatkan Pengetahuan Seksualitas Remaja - Nazarlin, Nazarlin; Raffles, Fatihah; Martin, Sri Novia; Rahmi, Iftita (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Sex education is crucial for adolescents from an early age, as they are vulnerable to misinformation about sexuality. This study aimed to examine adolescents' perceptions of sex education and provide psychoeducation to prevent risky sexual behavior. The methods used included lectures and discussions, with measurements conducted using a sexual behavior tendency scale through a pre-test, post-test, and a follow-up one month after the intervention. The results showed a significant increase in adolescents' knowledge levels after psychoeducation, with t = -15.282 (p = 0.000) for the pre-test and post-test comparison, and significant stability in the follow-up (t = -9.473, p = 0.000). Psychoeducation helps individuals recognize the importance of sex education without stigma. This program effectively fosters a healthy understanding and a positive attitude toward sexuality. Therefore, broader implementation is necessary, both in schools through the integration of sexual psychoeducation materials and in communities using an environment-based approach.